Language Anxiety And Its Effects On Speaking Performance Among Efl Learners (Texas Journal of Philology, Culture and History, 2025)
Language anxiety is a significant affective factor influencing foreign language learning, especially in speaking. This study examines the nature, sources, and impact of language anxiety on EFL learners’ speaking performance. Using a mixed-methods approach, quantitative data from the Foreign Language Classroom Anxiety Scale (FLCAS) were combined with qualitative insights from semi-structured interviews and classroom observations. Results show that high anxiety is strongly associated with reduced fluency, accuracy, vocabulary range, and overall communicative competence. Anxiety stems from fear of negative evaluation, low self-perceived proficiency, perfectionism, and classroom expectations. Highly anxious learners exhibited avoidance, frequent pauses, self-monitoring, and lower willingness to communicate. The study highlights the importance of supportive classroom practices, collaborative speaking tasks, and strategies to reduce anxiety. Future research should explore longitudinal changes, younger learners, and real-time cognitive processes during speaking